2013
DOI: 10.1155/2013/436263
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothermia Reduces Toll-Like Receptor 3-Activated Microglial Interferon-βand Nitric Oxide Production

Abstract: Therapeutic hypothermia protects neurons after injury to the central nervous system (CNS). Microglia express toll-like receptors (TLRs) that play significant roles in the pathogenesis of sterile CNS injury. To elucidate the possible mechanisms involved in the neuroprotective effect of therapeutic hypothermia, we examined the effects of hypothermic culture on TLR3-activated microglial release of interferon (IFN)-β and nitric oxide (NO), which are known to be associated with neuronal cell death. When rat or mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…With the aim of elucidating the possible mechanisms underlying the neuroprotective effects of therapeutic hypothermia, we have previously shown that hypothermia reduces the production of earlyphase and late-phase inflammatory factors as well as that of late-phase anti-inflammatory factor in primary microglia in vitro [33][34][35][36]. We considered that an approach using microglia removed directly from injured brains may yield more clinically relevant information.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the aim of elucidating the possible mechanisms underlying the neuroprotective effects of therapeutic hypothermia, we have previously shown that hypothermia reduces the production of earlyphase and late-phase inflammatory factors as well as that of late-phase anti-inflammatory factor in primary microglia in vitro [33][34][35][36]. We considered that an approach using microglia removed directly from injured brains may yield more clinically relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05 compared with 37°C. therapeutic hypothermia [33][34][35][36]. IL-10 has been considered to be neuroprotective because it reduces the production of pro-inflammatory cytokines [8,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations